Sacrificial bonds enhance toughness of dual polybutadiene networks. (22nd March 2016) - Gold, Barbara J.; Hövelmann, Claas H.; Weiss, Christine; Radulescu, Aurel; Allgaier, Jürgen; Pyckhout-Hintzen, Wim; Wischnewski, Andreas; Richter, Dieter
Abstract: A new dual network elastomer is developed that consists of polybutadiene crosslinked with both permanent and transient bonds. The transient network is formed by the association of urazole groups that are randomly attached to the polymer backbone. Subsequent orthogonal covalent crosslinking through hydrosilylation in the melt state leads to a dual network with variable permanent and transient crosslinking density. Small angle neutron scattering (SANS) investigations show a homogeneous distribution of the transient bonds in both the functionalized polymers and the dual network products. The enhanced mechanical properties of the dual networks compared to conventional polybutadiene elastomers are characterized by stress–strain measurements. The increased toughness can be explained by a protective mechanism where the weaker supramolecular bonds act as sacrificial bonds that dissipate energy. Graphical abstract: Highlights: Synthesis of permanent/transient dual polybutadiene networks. No change in Gaussian chain conformation compared to linear chains proven by small angle neutron scattering. Stress–strain measurements and Mooney–Rivlin analysis for mechanical characterization. Enhanced mechanical properties result from transient sacrificial bonds.